Bibliometric approach to entrepreneurial education - Fernández-Portillo, Antonio (Journal of Management and Business Education, 2018)
This introduction provides a current vision of the situation in which research on entrepreneurship education is located. For this, a review of the state of the question in entrepreneurial education is developed. This analysis allows to interconnect the previous issue of the Journal of Management and Business Education (JMBE), with the current one and to remain within its mission, objectives and main characteristics, which cc explained below. Finally, the third issue of the journal is presented.